TRADISI INGKUNGAN DI DESA TIRTOSARI YOGYAKARTA DALAM PANDANGAN AKIDAH ISLAM - Firza Khofifah (Academic Journal of Islamic Principles and Philosophy, 2021)
The Ingkungan tradition ceremony is held once a year on the eve of Eid al-Fitr. This ceremony is a form of salvation carried out by the people of Tirtosari Village by serving wuduk Rice and Ingkung chicken as offerings cooked by each family. This study examines the symbolic meaning in Ingkungan traditions and knowing the practice of Ingkungan traditions in Tirtosari Village according to Islamic faith or belief. This study uses a descriptive method, The data analysis technique uses Miles and Huberman, namely by going through the process of data reduction, data presentation, and drawing conclusions. The results show that the Uborampe used is still related with the nuances of Kejawen Islam such as Nasi wuduk is symbolized to achieve a real life through getting closer to God, while the Ingkung chicken symbolizes the main ideals that are realized by always n'jungkung (kneeling) and obtained by always manekung (muá¸¥Äsabah, khalwat, I'tikÄf, semedi, and taá¸¥annuá¹¡). In accordance with Islamic teachings, the Ingkungan tradition is good following by á¹£adaqah, creating harmony among residents, reading á¹¬akbÄ«r, TahlÄ«l, praying to Allah as a way to get closer to Allah.